Clinical, radiological and pathological evaluation of residual disease in women receiving neoadjuvant chemotherapy for locally advance carcinoma breast - Mishra, Mayank; Singh, Puspendra; Tripathi, Alok (International Surgery Journal, 2018)
Background: Egyptians were first to note this disease, 3,500 years ago and described fairly accurately in George Ebers papyri. This disease occurs almost entirely in women, but men can get it, too. Breast cancer is most common among women worldwide. In India, its second after cancer cervix. Its incidence outranks all other cancers in women >35 years of age. Age adjusted incidence rates vary from 9.7- 28.2/100,000. The treatment of locally advanced breast cancer has considerably changed and now includes a multidisciplinary approach, which is directed both to locoregional control and destruction of distant micro-metastasis. Neoadjuvant therapy causes a reduction in size of primary tumor allowing more conservative surgical approach without any increase in locoregional recurrence rate. Limitations of clinical methods for assessment of response to neoadjuvant chemotherapy have now incorporated by imaging and pathological method. Methods: In present study author assess LABC clinically, radiologically and pathologically by mammography USG, FNAC and histopathologic examination, pre- and post-neoadjuvant chemotherapy and evaluate response to chemotherapy, reduction of tumor volume and prior assessment of the patient’s prognosis. Results: Present study shown USG is more accurate in assessing residual disease in post neoadjuvant chemotherapy in defining the real extent of residual disease and also superior in term of detecting complete pathological response. Conclusions: A multimodal assessment of response of neoadjuvant chemotherapy is needed to direct optimal surgical treatment with acceptable cosmesis.